2022
DOI: 10.48550/arxiv.2205.15543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AI-based automated Meibomian gland segmentation, classification and reflection correction in infrared Meibography

Abstract: Purpose: Develop a deep learning-based automated method to segment meibomian glands (MG) and eyelids, quantitatively analyze the MG area and MG ratio, estimate the meiboscore, and remove specular reflections from infrared images. Methods: A total of 1600 meibography images were captured in a clinical setting. 1000 images were precisely annotated with multiple revisions by investigators and graded 6 times by meibomian gland dysfunction (MGD) experts. Two deep learning (DL) models were trained separately to segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Specular reflections in images of the MG can occur due to various factors such as the lighting conditions during imaging or the surface properties of the palpebral conjunctival tissues. 22 These reflections can obscure the visibility of the MG and affect the accuracy of analysis. Therefore, it was important to develop an automated algorithm to effectively remove these reflections.…”
Section: Methodsmentioning
confidence: 99%
“…Specular reflections in images of the MG can occur due to various factors such as the lighting conditions during imaging or the surface properties of the palpebral conjunctival tissues. 22 These reflections can obscure the visibility of the MG and affect the accuracy of analysis. Therefore, it was important to develop an automated algorithm to effectively remove these reflections.…”
Section: Methodsmentioning
confidence: 99%
“…Many recent studies have found that local features are more effective in describing an image's detailed and stable information [30][31][32][33][34]. Among these local features, Scale Invariant Feature Transform (SIFT) is one of the popular in the field of biometrics.…”
Section: B Elimination Methods To Remove Unwanted Imagesmentioning
confidence: 99%